Sydney - Womersley, Steve; Neustein, Rachel; Gale Group (London Dorling Kindersley Limited, 2015)
Provides background information on Sydney, Australia. Recommends the 10 best restaurants, bars, nightlife, neighborhoods, hotels, and local attractions.
Sydney's top 10 -- Around town -- Streetsmart.
Includes bibliographical references and index.
Keywords: Sydney (N.S.W.) -- Guidebooks